Markets, Social Embeddedness and Precapitalist Societies: the Case of Village Tradestores in Papua New Guinea - Curry, George (1999)
The village tradestore in rural Papua New Guinea is a physical expression of modernity in the heart of the village and is symbolic of the new economic and social formations associated with incorporation. This paper examines how the village tradestore is positioned in relation to these processes of change by considering the management and operation of several tradestores in the Wosera sub-district, East Sepik Province. The paper reports on the ways in which values, relationships and behaviours associated with both the introduced market economy and the precapitalist socio-economy become articulated through the ostensibly modern phenomenon of tradestores.